Analysis of factors impeding access to finance in internet enabled crowdfunding: a systematic literature review. (19th July 2022) - Green, Emma; Sukumar, Arun; Jafari-Sadeghi, Vahid; Pandya, Kaushik; Khavarinezhad, Sepideh
Internet enabled crowdfunding (IECF) is evolving fast to become a global phenomenon and has an increasingly important role in the financing of entrepreneurs. The debate around problems faced by entrepreneurs in securing funding through IECF is reviewed in this paper. Through a systematic literature review (SLR), the paper explores the themes emerging from the review and discusses the emerging issues that prevent access to funding through crowdfunding platforms. Research suggests a lack of access to funding as being a fundamental problem faced by entrepreneurs, but this paper goes beyond the identification of traditional barriers and focuses on issues that are emerging because of the innovative use of Web 2.0. Further, it concludes with practice and policy implications on the emergence of new barriers for entrepreneurs.